Character Wayang Timplong of Panji Asmarabangun Figure and its Relevance to the Pancasila Students’ Profile - Riski Utma Dona; Mulyanto Mulyanto; Margana Margana (AL-ISHLAH: Jurnal Pendidikan, 2023)
As the nation's potential candidates, the young generation is abandoning their value-rich regional cultures in favour of foreign cultures such as K-Pop one of the affected cultures is wayang Timplong. This study analyzes about what are the visual meanings and character education values contained in the Timplong puppet, the character Panji Asmarabangun and its relevance to the Pancasila Students' Profile. This study was to determine the value of character education in the wayang Timplong of Panji Asmarabangun figure based on the visual form of the objective. This was designed with a qualitative approach, data were collected through interviews, observations, and document analysis. The study was carried out in Kepanjen, Pace and in Nglawak, Prambon, Nganjuk Regency. The informants of this research are 3 dalang and a craftsman. The data analysis technique in this study used the Interactive Model. The results showed that the visual form of Wayang Panji Asmarabangun consists of the head, body, and clothing consisting of the gabahan eyes, ambangir nose, damis mouth, torso putro sariro, satria arm, bokongan satria, suku bambang feet, rapakan bolo clothes, keris, wadyo bracelet. The character education values were religious, nationalist, independent, mutual cooperation, integrity, simple, innocent, noble, virtuous, holy, smooth, tough, and skilled. The relevance to the profiles of Pancasila students is a) having faith, fearing God Almighty, having noble character; independence; mutual cooperation; global diversity; critical reasoning; and creativity. This study provides information in the form of characters possessed by Panji Asmarabangun, and character can be used as a reference/material in teaching and instilling character education values based on local culture that are in line with those encapsulated in Pancasila students' profiles in the independent curriculum, so that can be a trigger for student appreciation, — especially in the Nganjuk region.